The Eguren family in Peru: The poet's brothers - López Eguren, Isabel Cristina (2014)
In this article, the author highlights unknown aspects of the life of José María Eguren and his family. By correcting inaccurate information that has been widely disseminated and adding data previously ignored, it describes the career of Isaac and Jorge Luis Eguren, both brothers of the poet. The researcher stresses the participation of both characters in the cultural, social and economic life of Peru at critical junctures. It also links Isaac and Jorge Luis with leading political personalities of their time.